(untitled) (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2023)
In this article, research was conducted by the tax service authorities on ways to improve the methodological basis of tax control and tax audits and evaluate their effectiveness, and conclusions and suggestions were formed within the framework of the research.